(untitled) (Research, Society and Development, 2022)
Cardiac toxicity is severe and an adverse effect of many chemotherapy drugs. The following guiding research question used was: how does the nurse provide health care for prevention and treatment of chemotherapy induced cardiotoxicity? This study is an Integrative Literature Review of which articles were searched in the Scielo, PubMed and BVS databases. The inclusion criteria were complete texts in Portuguese, English, and Spanish, published within a five-year period and indexed with the used keywords. The exclusion criteria were incomplete texts published over five years. The research indicates that there is a need of increasing the literary productions on the theme as well as a need of creating specific tools and guidelines to help nurses and the health care team to coordinate the care of cancer patients with cardiotoxicities generated by chemotherapeutic agents. It was also revealed that the nurse, as the only member of the health team that assists the patient in its entirety and in a holistic manner, has a crucial role in the management of risk factors, being able to act in the detection of the appearance of new signs and symptoms in the patients’ routine, as well as guidance to eliminate or minimize their damage.